Fantasy, dream, vision, and hallucination: Approaches from a parallactic neuro-psychoanalytic perspective. Issue 1 (2nd January 2018) - Goetzmann, Lutz; Ruettner, Barbara; Siegel, Adrian
ABSTRACT: In this paper, we present a model of a specific category of complex thought and memory processes – figurative representations – which are viewed from a parallactic, psychoanalytic and neurobiological perspective. We postulate that figurative representations can be understood as the products of a complex memory process. Modern memory research distinguishes between a "dispositional space" containing the blueprints for producing representations, and the "image space" in which these representations are fabricated; in other words, between the "archive" and the "workshop" of memory. The selective retrieval of specific memories and the transformation of the Remembered permit the creative formation of different types of figurative representations such as fantasies, dreams, visions and hallucinations. Both cognitive and affective processes can contribute to the differences between these types of representations. Depending on the intensity with which reality is perceived, figurative representations may appear as dreams or fantasies, visions or hallucinations. These transformations can be traced on the basis of known dreams and hallucinations which Freud described in his work, From the History of an Infantile Neurosis . We suggest that parallactic points of view, although nearly identical to one another, are nevertheless wholly incompatible: this gap is inherent in every parallactic model, and possibly has a determining influence on postmodern subjectivity.